Median Nerve Neuropathy Caused by Persistent Median Artery Thrombosis - Yusuke Miyashima, MD; Hiroyuki Gotani, MD, PhD; Kotaro Okamoto, MD; Hirohisa Yagi, MD; Yoshitaka Tanaka, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Persistent median artery thrombosis mimicking carpal tunnel syndrome is rare. Here, we report the pathological, ultrasonography, and intraoperative findings of a case of persistent median artery thrombosis mimicking carpal tunnel syndrome. A 34-year-old man reported to our clinic with a complaint of numbness in his left thumb, index finger, and middle finger, which are innervated by the left median nerve. He also reported that he felt pain in his left wrist and distal forearm while working. Although findings of the usual provocative tests and nerve conduction studies were normal, ultrasonography revealed arterial thrombosis at the carpal tunnel level, whereas magnetic imaging showed persistent median artery thrombosis in the carpal tunnel. Three months after surgical resection of the thrombosed section of the artery, the patient fully recovered with no residual pain or limitations in the use of the affected arm. His patient-reported outcomes improved as well. It is important to investigate the existence of persistent median artery thrombosis if a patient presents with atypical symptoms of carpal tunnel syndrome. Ultrasonography is useful for the diagnosis of persistent median artery thrombosis. Surgical resection of a thrombosed persistent median artery in patients with carpal tunnel syndrome yields good results.